Opusc nawiasy i wykonaj redukcje wyrazow podobnych

c) (4x + 5y) - (3x - 0,5y)
d) (y² + 5y - 6) + (2y² - y + 8)
e) 4a(5b - a) - 4(2a² - 2ab)
f) (2x - 0,2) - (3x + 0,5)
g) -5x - (-2x - 7)
h) -5x + (-2y + 4x)

Niech ktos to zrobi, to proste ale ale ja zapomnialem jak co ma isc ;)

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-09T20:59:31+01:00
C) (4x + 5y) - (3x - 0,5y)=4x + 5y -3x + 0,5y = x + 5,5y
d) (y² + 5y - 6) + (2y² - y + 8) = y² + 5y - 6 + 2y² -y + 8 = 3y² + 4y +2
e) 4a(5b - a) - 4(2a² - 2ab)= 20ab - 4a² - 8a² + 8ab = 28ab - 12a²
f) (2x - 0,2) - (3x + 0,5)= 2x - 0,2 - 3x - 0,5 = -x -0,7
g) -5x - (-2x - 7) = -5x +2x + 7 = -3x + 7
h) -5x + (-2y + 4x) = -5x - 2y + 4x = x - 2y
3 3 3
2009-11-09T21:42:49+01:00
C) (4x + 5y) - (3x - 0,5y) = 4x + 5y -3x + 0,5y = x + 5,5y

d) (y² + 5y - 6) + (2y² - y + 8) = y² + 5y - 6 + 2y² - y + 8 = 3y² + 4y + 2

e) 4a(5b - a) - 4(2a² - 2ab) = 20ab - 4a² - 8a² + 8ab = 28ab - 12a²

f) (2x - 0,2) - (3x + 0,5) = 2x - 0,2 - 3x - 0,5 = -x - 0,7

g) -5x - (-2x - 7) = -5x +2x + 7 = -3x + 7

h) -5x + (-2y + 4x) = -5x - 2y + 4x = x - 2y
1 5 1